Techniques for Studying Materials, Examination of an Artefact - Rutter Noel; Yeoh Catriona; Barber Zoe; Durrell John; DoITPoMS, University of Cambridge
Este grupo de animaciones proporciona una gua̕ para el anl̀isis fs̕ico y virtual de un artefacto. Comprende los siguientes elementos:Evolution of deformation microstructure Polymer identification chart Infra red spectra for common polymers Simple examination of a composite Virtual examination of an artefact Visually identifying different metals: quiz